Penggunaan Tumbuhan Obat Sebagai Penunjang Kesehatan pada Masyarakat Betawi - Hendri Aldrat; Winda Trya Wulandari; Mita Restinia (UIN Syarif Hidayatullah Jakarta, 2023)
Changes in land use from rice fields and plantations to residential areas, offices, and trading complexes will certainly result in changes in the biodiversity of the environment of the inhabitants of the capital city of Jakarta, including the Betawi community. The scarcity of certain species due to land conversion also affects people’s ethnobotanical knowledge. This study aimed to explore how the Betawi people, with the rapid flow of urbanization, use medicinal plants around them. A total of 25 respondents of the selected Betawi ethnicity were interviewed about the use of medicinal plants. Purposive sampling and snowball sampling were used. The data obtained from the respondents were collected and compared using triangulation techniques with previously published ethnobotanical reports. The results showed that as many as 61 species from 36 families were used by the Betawi people to support their health. Ginger, lemongrass, and jatropha are the most widely used plants. The most widely used species belong to the Zingiberaceae family. The most commonly used part is the leaves (55%), the most common processing method is boiling (48%), the most common way to administer the medicine is by drinking (49%), and as much as 61% of medicinal plants are used in the home. In conclusion, the Betawi people still maintain the tradition of using herbal medicine amidst the high rate of urbanization in the capital city of Jakarta. Furthermore, it is necessary to conduct further experiments in the laboratory to validate the safety, efficacy, and identification of the active ingredients in these plants.